ECONOMIC STRATEGIES OF PALM OIL FARMERS DURING THE REPLANTING PERIOD IN NAGARI SIPANGKUR, DHARMASRAYA REGENCY - Vita Ari Wahyuni; Firdaus Firdaus; Sri Rahmadani (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Replanting is an essential step in maintaining palm oil productivity due to aging plants. However, this process causes a drastic decrease in farmers' income, up to 65% during the 3-5 years waiting period for harvest. This study aims to assess the socio- economic impacts and fulfillment strategies undertaken by farmers during the palm oil replanting period in Nagari Sipangkur, Tiumang District, Dharmasraya Regency. This research uses a qualitative approach with a descriptive type. Data collection techniques were carried out through observation, in-depth interviews with 12 informants selected by purposive sampling, and document studies. Data were analyzed using the Miles and Huberman approach of data collection, data reduction, data presentation, and conclusion drawing. James S. Coleman's rational choice theoretical framework was used to analyze farmers' strategic choices in meeting their needs. The results showed that farmers chose three main strategies to fulfill their needs during the replanting period. These strategies are occupational strategies by shifting the main job, maximizing asset potential and making efficiency. These strategies reflect farmers' adaptation and resilience in facing economic challenges during replanting. Therefore, this study concludes that in the implementation of replanting, it is very important to build farmers' rationality in maximizing the assets they have to get around economic challenges.